Upaya Peningkatan Pemasaran Digital melalui Konten Instagram untuk Meningkatkan Minat Pembelian pada UD Puji Bakery - Ardhana, Muhammad Nauval; Yulianto, Mochamad Rizal (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in supporting economic growth and job creation. However, the limited use of digital media as a promotional tool remains an obstacle in expanding the marketing reach of MSME products. This activity was carried out at UD Puji Bakery, a bread distributor business that markets various types of bread products, with the aim of optimizing Instagram as a digital promotional medium to expand marketing reach and encourage customer purchasing interest. The implementation method includes observing partner marketing conditions, managing Instagram accounts, planning and creating promotional content, publishing content, and evaluating responses to digital marketing activities. The evaluation was carried out by observing market responses indicated by the number of orders and interactions with promotional activities. The results of the activity showed that the use of Instagram can support UD Puji Bakery's promotional activities and contribute to the emergence of large orders. Among them, Nana bread products reached orders of 3,600 pcs distributed to Porong Market through three shipments, while Winy bread products reached 2,750 pcs or 55 cartons. This shows that the use of Instagram has potential as a digital promotional medium that can support marketing expansion and increase demand for MSME products. This activity can be one strategy that MSMEs can implement to optimize the use of social media as a digital marketing tool to increase the effectiveness of their reach and interaction with consumers.